2017
DOI: 10.1080/0142159x.2017.1279278
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to promote resilience, empathy and well-being in the health professions: Insights from the 2015 CENTILE Conference

Abstract: The high prevalence of physician burnout is of great concern and may begin with observed declines in empathy and increases in stress and burnout in medical and health professions students. While underlying causes have been described, there is less certainty on how to create effective interventions in curricula and workplace. In October 2015, The Center for Innovation and Leadership in Education (CENTILE) at Georgetown University, together with MedStar Health, Georgetown's clinical partner, and six academic ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 10 publications
0
19
0
2
Order By: Relevance
“…Our realist analysis developed and refined 19 context-mechanism-outcome configurations in the data set. This analysis demonstrated that doctors are more likely to experience mental ill-health when they feel isolated, when they feel unable to do the job they were trained for and when they fear the repercussions of seeking help and support (this was demonstrated in context-mechanism-outcome configurations [1][2][3][4][5][6]. Interventions that emphasised relationships and belonging (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our realist analysis developed and refined 19 context-mechanism-outcome configurations in the data set. This analysis demonstrated that doctors are more likely to experience mental ill-health when they feel isolated, when they feel unable to do the job they were trained for and when they fear the repercussions of seeking help and support (this was demonstrated in context-mechanism-outcome configurations [1][2][3][4][5][6]. Interventions that emphasised relationships and belonging (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Rothernberger 2 The growing incidence of mental ill-health in health professionals, including doctors, across specialties and throughout careers 3 is a major issue in many countries. [4][5][6][7][8][9] We use 'mental ill-health' as a broad term to encompass a variety of conditions, including psychological distress, stress, burnout, depression, addiction and suicide (see also Chapter 3, Terminology). A study conducted by American Medical Association and Mayo Clinic researchers in 2014 reported that 54% of physicians in the USA are experiencing professional burnout.…”
Section: Discussionmentioning
confidence: 99%
“…How is resiliency cultivated? Suggestions for fostering resiliency published in the literature include being flexible, acting to remove or mitigate stress contributors, remaining connected with your work community, finding ways to release physical and emotional tension, identifying your personal sense of purpose, participating in projects that are meaningful to you, and developing and adhering to healthy habits (57)(58)(59)(60)(61)(62)(63)(64)(65)(66). Unfortunately, even for highly resilient individuals, unless the obstacles are removed or altered, the ability to bounce back is more challenging, if not impossible (67).…”
Section: Reboot and Refocus-halvorsonmentioning
confidence: 99%
“…Connotados expertos en el tema insisten que ya es tiempo que cambiemos el discurso del burnout al bienestar 28,[31][32] ; para lo cual es preciso reconocer que nos cabe una responsabilidad en el desgaste de nuestros estudiantes y que tenemos una obligación ética para con ellos y sus pacientes 15 .…”
Section: Conclusionesunclassified